Knowledge and project management : a shared approach to improve performance - Handzic, Meliha; Bassi, Antonio (Knowledge management and organizational learning (Series) ;, 2017)
This book argues that by integrating effective knowledge management (KM) with project management (PM), the overall project success rate can be improved significantly. It brings together the latest ideas and research on shared approaches to improve performance based on the research and experience of academics and practitioners. The structured collection of articles presents novel theoretical approaches and clear empirical evidence of the value of integrating the two distinct fields. It enables readers to better understand the need to merge KM with PM and appreciate the benefits. It also offers researchers an idea of what lies ahead and how to get there, and helps practitioners develop more suitable KM solutions for successful project outcomes.